Aplikasi sistem informasi geografis untuk pemetaan kerentanan kuantitas mata air dan pengaruhnya terhadap budidaya kopi di Kecamatan Grabag, Kabupaten Magelang. - Cherlin Rian Rosalia; Muchlis Muchlis; Arie Noor Rakhman (JNANALOKA, 2022)
The springs in Grabag Sub-district have decreased the quantity of water because of a large amount of water taken from the springs by the residents and PDAM. This can threaten the volume of existing springs. This study aims to analyze the quantity vulnerability of the spring area and identify the conservation in the management of springs in the study area by using a Geographic Information System (GIS) application. The data used is the observation of data in the field and laboratory. Data as soil type, morphometry, constituent lithology, land use, vegetation, water discharge, access, and use of water. We classify the vulnerability of springs in the study area as low - medium vulnerability. Areas of low vulnerability, vulnerability class 2.0–2.6 are scattered in the springs of Tuk Ngrancah, Tuk Tlogosari, Tuk Gedad, and Tuk Tlogorejo. This area is composed of colluvial deposits of regosol soil, low rainfall (1750–2250 mm/year), sloping slopes (9-15°), and they used the land as gardens. Medium classification areas, with vulnerability class 2.7–3.3 spread over the springs of Tuk Bleder, Tuk Mas Kalimas, Tuk Kembar, and Tuk Udal. This area is composed of colluvial deposits of latosol soil, moderate rainfall (2250-2750 mm/year), undulating slopes (16-25°), and land use as gardens. The direction of spring conservation techniques is as agronomic conservation techniques with vegetative methods. The application of this method to springs with low vulnerability classification is the use of bamboo (Bambusa sp.) as a ground cover plant. Coffee liberika (Coffea liberika) together with lamtoro (Leucaena leucochephala) and sugar palm (Arenga pinnata) were directed to springs with moderate susceptibility classification. The existence of agro-tourism land through coffee cultivation is the direction of agronomic conservation techniques in Grabag District.